2017
DOI: 10.1002/cctc.201700127
|View full text |Cite|
|
Sign up to set email alerts
|

Silica‐Supported Au–Ag Catalysts for the Selective Hydrogenation of Butadiene

Abstract: Gold and silver are miscible over the entire composition range, and form an attractive combination for fundamental studies on bimetallic catalysts. Au–Ag catalysts have shown synergistic effects for different oxidation and liquid‐phase hydrogenation reactions, but have rarely been studied for gas‐phase hydrogenation. In this study 3 nm particles of Au, Ag and Au–Ag supported on silica (SBA‐15) were investigated as catalysts for selective hydrogenation of butadiene in an excess of propene. The Au catalyst was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…A lower activity for Au/SiO 2 than for Au/TiO 2 for the hydrogenation of butadiene has been also reported by Haruta et al (TOF of 6 × 10 −3 s −1 for the Au/SiO 2 versus 20 × 10 −3 s −1 for the Au/TiO 2 (particle sizes of 7.0 ± 3.0 and 3.5 ± 1.3, respectively) at 150 °C). 69 , 70 The lower activity seems specific for SiO 2 supports since higher and very similar activities were found for Au on Al 2 O 3 , ZrO 2 and CeO 2 as well as for Au on TiO 2 by Louis et al 26 Kinetic studies showed that the apparent activation energy for Au catalysts on different supports, including SiO 2 and TiO 2 , does not depend on the support, 26 , 71 suggesting that similar active sites are present in all supported Au catalysts. There is consensus in literature that H 2 dissociation is the rate-determining step for hydrogenation reaction, but no clear consensus on which sites are the most active ones.…”
Section: Results and Discussionmentioning
confidence: 87%
“…A lower activity for Au/SiO 2 than for Au/TiO 2 for the hydrogenation of butadiene has been also reported by Haruta et al (TOF of 6 × 10 −3 s −1 for the Au/SiO 2 versus 20 × 10 −3 s −1 for the Au/TiO 2 (particle sizes of 7.0 ± 3.0 and 3.5 ± 1.3, respectively) at 150 °C). 69 , 70 The lower activity seems specific for SiO 2 supports since higher and very similar activities were found for Au on Al 2 O 3 , ZrO 2 and CeO 2 as well as for Au on TiO 2 by Louis et al 26 Kinetic studies showed that the apparent activation energy for Au catalysts on different supports, including SiO 2 and TiO 2 , does not depend on the support, 26 , 71 suggesting that similar active sites are present in all supported Au catalysts. There is consensus in literature that H 2 dissociation is the rate-determining step for hydrogenation reaction, but no clear consensus on which sites are the most active ones.…”
Section: Results and Discussionmentioning
confidence: 87%
“…Lastly, a comparison with the literature reveals that the propene conversion values here obtained ( Figure 6 A) are drastically lower than that for other Cu-based catalysts in the literature (0.1–1%), as measured under similar reaction conditions (Cu/TiO 2 , 46 Cu–Zn/TiO 2 , 35 Cu–Au/TiO 2 , and Au/TiO 2 6 ). Our Cu/SiO 2 systems also outperform Pd-based NPs (generally >1% propene conversion, same conditions), 54 single-atom Pd and Pt/Cu (∼0.1 and ∼1% propene conversion; corresponding gas feed: 1.9/2% butadiene, 70/20% propene, 4.7/16% hydrogen and balance He, respectively), 55 , 56 Au/SiO 2 catalysts (for which the conversion of propene was already particularly low, <0.1%, same conditions), 37 , 40 or PdAu bimetallic nanorods (selectivity to butenes below 90%, same conditions). 54 To the best of our knowledge the highest butenes selectivity (>98%) under similar conditions was reported for Cu-based catalysts obtained via carbonization of MOFs (HKUST-1, 50 wt % Cu).…”
Section: Results and Discussionmentioning
confidence: 92%
“… 8 , 10 15 The exact atomic distribution of the metals is particularly important in catalysis, in which the atoms close to the surface play a dominant role in the catalytic performance. 7 , 16 19 Furthermore, when exposing bimetallic nanoparticles to various gas atmospheres and heating them to elevated temperatures, atomic redistribution can occur. 11 , 17 , 18 , 20 26 This alters the optical 8 , 13 , 26 and catalytic properties 16 18 , 24 , 27 and can even lead to severe deactivation of the catalyst.…”
mentioning
confidence: 99%